Hormonal Contraceptive Use as Risk Factor for Breast Cancer in Young Javanese Women - Luna Fitria Kusuma; Kristanto Yuli Yarso (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Previous study from 351 Indonesian women shown that they had breast cancers at younger age compared with western. In this study we investigate role of hormonal contraceptive as risk factor for Indonesian Javanese young breast cancer cases. However, the presence different life style between ethnic alter their risk as causal factors across populations. Diagnostic and prognostic study findings, including breast cancer prediction rules, must therefore be validated in Asian women. We undertook case-control study to determine population-based distributions of breast cancer among young Javanese people, one of the largest populations in Indonesia (Southeast Asia). A total of 500 women diagnosed with breast cancer participated in this study, divided in to two group young (less 40 years old) and mature breast cancer. Data for hormonal contraceptive, clinico-pathological characteristics and other risk factors were collected. We found that young Javanese women who use hormonal contraceptive for more than 10 years had a 4,67 fold increased risk of being diagnosed with breast cancer in young age (p<0,01). We didn’t found any differences between this two groups in menarche and parity. Interestingly for Javanese women who breast feeding more than 18 months increase 1,74 fold increased risk of being diagnosed with breast cancer in young age (p<0,01).